Analyse und Optimierung des Korrosions- und Alterungsverhaltens von hybriden Strukturen aus Metallen und CFK - Grothe, R.; Striewe, Jan André; Kowatz, Jannik; Grundmeier, Guido; Tröster, Thomas; Meschut, Gerson

Water adsorption and capillary bridge formation on silica micro-particle layers modified with perfluorinated organosilane monolayers - Giner, Ignacio; Torun, Boray; Han, Yan; Duderija, Belma; Meinderink, Dennis; Orive, Alejandro González; de los Arcos de Pedro, Maria Teresa; Weinberger, Christian; Tiemann, Michael; Schmid, Hans-Joachim; Grundmeier, Guido (Applied Surface Science)
Monodisperse micron-sized silica particle monolayers deposited onto plasma-grown SiOx-ultra-thin films have been used as reference systems to investigate wetting, water adsorption and capillary bridge formation as a function of silica surface functionalization. 1H,1H, 2H,2H perfluorooctyltriethoxysil (FOTS) monolayers, have been deposited on the respective surfaces by means of chemical vapor deposition resulting in macroscopically low energy surfaces. X-ray photoelectron spectroscopy (XPS) and Fourier transform infrared (FTIR) reflection absorption spectroscopy confirmed the monolayer formation. Water adsorption isotherms were studied by a combination of in-situ FTIR reflection spectroscopy and quartz crystal microbalance (QCM) while macroscopic wetting was analysed by contact angle measurements. The comparative data evaluation indicates that the macroscopic wetting behaviour was changed as expected, however, that water nanodroplets formed both at intrinsic defects of the FOTS monolayer and at the FOTS/SiOx interface. Capillary bridges of liquid water are dominantly formed in the confined particle contact areas and between surface asperities on the particles. The comparison of wetting, adsorption and capillary bridge formation shows that the hydrophobization of porous materials by organosilane monolayers leads to the formation of morphology dependent nanoscopic defects that act as sites for preferential capillary bridge formation.

Dynamics of DNA Origami Lattice Formation at Solid–Liquid Interfaces - Kielar, Charlotte; Ramakrishnan, Saminathan; Fricke, Sebastian; Grundmeier, Guido; Keller, Adrian (ACS Applied Materials & Interfaces)

Structural stability of DNA origami nanostructures under application-specific conditions - Ramakrishnan, Saminathan; Ijäs, Heini; Linko, Veikko; Keller, Adrian (Computational and Structural Biotechnology Journal)

Pharmacophore Nanoarrays on DNA Origami Substrates as a Single-Molecule Assay for Fragment-Based Drug Discovery - Kielar, Charlotte; Reddavide, Francesco V.; Tubbenhauer, Stefan; Cui, Meiying; Xu, Xiaodan; Grundmeier, Guido; Zhang, Yixin; Keller, Adrian (Angewandte Chemie International Edition)

Superstructure-Dependent Loading of DNA Origami Nanostructures with a Groove-Binding Drug - Kollmann, Fabian; Ramakrishnan, Saminathan; Shen, Boxuan; Grundmeier, Guido; Kostiainen, Mauri A.; Linko, Veikko; Keller, Adrian (ACS Omega)

Directed Protein Adsorption Through DNA Origami Masks - Ramakrishnan, Saminathan; Grundmeier, Guido; Keller, Adrian (DNA Nanotechnology: Methods and Protocols)

On the Stability of DNA Origami Nanostructures in Low-Magnesium Buffers - Kielar, Charlotte; Xin, Yang; Shen, Boxuan; Kostiainen, Mauri A.; Grundmeier, Guido; Linko, Veikko; Keller, Adrian (Angewandte Chemie International Edition)

On the Adsorption of DNA Origami Nanostructures in Nanohole Arrays - Brassat, Katharina; Ramakrishnan, Saminathan; Bürger, Julius; Hanke, Marcel; Doostdar, Mahnaz; Lindner, Jörg; Grundmeier, Guido; Keller, Adrian (Langmuir)

Ultrasound-mediated deposition and cytocompatibility of apatite-like coatings on magnesium alloys - Liu, Chen-Ni; Böke, Frederik; Gebhard, Maximilian; Devi, Anjana; Fischer, Horst; Keller, Adrian; Grundmeier, Guido (Surface and Coatings Technology)

Adsorption and Fibrillization of Islet Amyloid Polypeptide at Self-Assembled Monolayers Studied by QCM-D, AFM, and PM-IRRAS - Hajiraissi, Roozbeh; Hanke, Marcel; Yang, Yu; Duderija, Belma; Gonzalez Orive, Alejandro; Grundmeier, Guido; Keller, Adrian (Langmuir)

Determination of the refractive indices of ionic liquids by ellipsometry, and their application as immersion liquids - Wu, Xia; Muntzeck, Maren; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido; Wilhelm, René; Wagner, Thorsten (Applied Optics)

Luminescent Nd2S3 thin films: a new chemical vapour deposition route towards rare-earth sulphides - Cwik, Stefan; Beer, Sebastian M. J.; Schmidt, Marcel; Gerhardt, Nils C.; de los Arcos de Pedro, Maria Teresa; Rogalla, Detlef; Weßing, Jana; Giner, Ignacio; Hofmann, Martin; Grundmeier, Guido; Wieck, Andreas D.; Devi, Anjana (Dalton Transactions)
Development of two new neodymium containing precursors and their successful implementation in the MOCVD of luminescent Nd2S3 thin films.

Improved homogeneity of plasma and coating properties using a lance matrix gas distribution in MW-PECVD - Kirchheim, Dennis; Wilski, Stefan; Jaritz, Montgomery; Mitschker, Felix; Oberberg, Moritz; Trieschmann, Jan; Banko, Lars; Brochhagen, Markus; Schreckenberg, Rabea; Hopmann, Christian; Böke, Marc; Benedikt, Jan; et al. (Journal of Coatings Technology and Research)

Validation of a Terminally Amino Functionalized Tetra‐Alkyl Sn(IV) Precursor in Metal–Organic Chemical Vapor Deposition of SnO 2 Thin Films: Study of Film Growth Characteristics, Optical, and Electrical Properties - Zanders, David; Ciftyurek, Engin; Hoppe, Christian; de los Arcos de Pedro, Maria Teresa; Kostka, Aleksander; Rogalla, Detlef; Grundmeier, Guido; Schierbaum, Klaus Dieter; Devi, Anjana (Advanced Materials Interfaces)

PEALD of SiO2 and Al2O3 Thin Films on Polypropylene: Investigations of the Film Growth at the Interface, Stress, and Gas Barrier Properties of Dyads - Gebhard, Maximilian; Mai, Lukas; Banko, Lars; Mitschker, Felix; Hoppe, Christian; Jaritz, Montgomery; Kirchheim, Dennis; Zekorn, Christoph; de los Arcos de Pedro, Maria Teresa; Grochla, Dario; Dahlmann, Rainer; Grundmeier, Guido; et al. (ACS Applied Materials & Interfaces)

PEALD of SiO2 and Al2O3 Thin Films on Polypropylene: Investigations of the Film Growth at the Interface, Stress, and Gas Barrier Properties of Dyads - Gebhard, Maximilian; Mai, Lukas; Banko, Lars; Mitschker, Felix; Hoppe, Christian; Jaritz, Montgomery; Kirchheim, Dennis; Zekorn, Christoph; de los Arcos de Pedro, Maria Teresa; Grochla, Dario; Dahlmann, Rainer; Grundmeier, Guido; et al. (ACS Applied Materials & Interfaces)

PEALD of SiO2 and Al2O3 Thin Films on Polypropylene: Investigations of the Film Growth at the Interface, Stress, and Gas Barrier Properties of Dyads - Gebhard, Maximilian; Mai, Lukas; Banko, Lars; Mitschker, Felix; Hoppe, Christian; Jaritz, Montgomery; Kirchheim, Dennis; Zekorn, Christoph; de los Arcos de Pedro, Maria Teresa; Grochla, Dario; Dahlmann, Rainer; Grundmeier, Guido; et al. (ACS Applied Materials & Interfaces)

Combined in situ infrared reflection absorption spectroscopy-quartz crystal microbalance investigation of the initial growth stages of plasma-deposited SiO x on polypropylene - Dietrich, J.; Hoppe, C.; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido (Contributions to Plasma Physics)

Decoupling of ion- and photon-activation mechanisms in polymer surfaces exposed to low-temperature plasmas - Budde, Maik; Corbella, Carles; Große-Kreul, Simon; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido; von Keudell, Achim (Plasma Processes and Polymers)

Water assisted atomic layer deposition of yttrium oxide using tris(N,N′-diisopropyl-2-dimethylamido-guanidinato) yttrium(iii): process development, film characterization and functional properties - Mai, Lukas; Boysen, Nils; Subaşı, Ersoy; de los Arcos de Pedro, Maria Teresa; Rogalla, Detlef; Grundmeier, Guido; Bock, Claudia; Lu, Hong-Liang; Devi, Anjana (RSC Advances)
A new water assisted atomic layer deposition (ALD) process was developed using the yttrium tris-guanidinate precursor which resulted in device quality thin films.

Comparative study on the deposition of silicon oxide permeation barrier coatings for polymers using hexamethyldisilazane (HMDSN) and hexamethyldisiloxane (HMDSO) - Mitschker, F; Schücke, L; Hoppe, Ch; Jaritz, M; Dahlmann, R; de los Arcos de Pedro, Maria Teresa; Hopmann, Ch; Grundmeier, Guido; Awakowicz, P (Journal of Physics D: Applied Physics)

Influence of average ion energy and atomic oxygen flux per Si atom on the formation of silicon oxide permeation barrier coatings on PET - Mitschker, F; Wißing, J; Hoppe, Ch; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido; Awakowicz, P (Journal of Physics D: Applied Physics)

Connection between target poisoning and current waveforms in reactive high-power impulse magnetron sputtering of chromium - Layes, Vincent; Corbella, Carles; Monjé, Sascha; Schulz-von der Gathen, Volker; von Keudell, Achim; de los Arcos de Pedro, Maria Teresa (Plasma Sources Science and Technology)

Analysis of polymer/oxide interfaces under ambient conditions – An experimental perspective - González-Orive, A.; Giner, I.; de los Arcos de Pedro, Maria Teresa; Keller, Adrian; Grundmeier, Guido (Applied Surface Science)

Analysis of polymer/oxide interfaces under ambient conditions – An experimental perspective - González-Orive, A.; Giner, I.; de los Arcos de Pedro, Maria Teresa; Keller, A.; Grundmeier, Guido (Applied Surface Science)

Analysis of polymer/oxide interfaces under ambient conditions – An experimental perspective - González-Orive, A.; Giner, I.; de los Arcos de Pedro, Maria Teresa; Keller, A.; Grundmeier, G. (Applied Surface Science)

Graphene oxide as flexibilizer for epoxy amine resins - Wolk, Andreas; Rosenthal, Marta; Weiß, Julia; Voigt, Markus; Wesendahl, Jan-Niklas; Hartmann, Marc; Grundmeier, Guido; Wilhelm, Rene; Meschut, Gerson; Tiemann, Michael; Bremser, Wolfgang (Progress in Organic Coatings)
Different types of reduced graphene oxide and graphene oxide particles have been studied regarding their influence on the curing behaviour of epoxy-amine resins. Especially the specific surface area of reduced graphene oxide was selectively influenced by controlled drying of the material. The different types of reduced graphene oxide particles were used to produce epoxy-amine composites that significantly change their curing behaviour and mechanical properties. A variety of surface areas and compositions were prepared by combination of a fast heating rate and different drying methods. The combination of freeze drying with a fast heating rate leads to a large specific surface area of 680 m2/g. The morphologies of the particles were observed by scanning electron microscope and the BET surface area was measured with nitrogen-physisorption. The exfoliation quality was measured by XRD. The generated graphene oxide and thermally reduced graphene oxide particles were mixed with epoxy-amine resin. The curing behaviour was studied with rheological and differential scanning calorimetry (DSC) measurements. We observed that different surface functionalities lowers the Glass transition temperature and the gel time of an epoxy-amine curing system. In addition, we found that generated graphene oxide acts as flexibilizer. An increase of the deformation from 2.5 mm to 3.1 mm was measured by Erichsen Cupping Test.

Corrosion properties of bioresorbable FeMn-Ag alloys prepared by selective laser melting - Wiesener, Markus; Peters, K.; Taube, Alexander; Keller, Adrian; Hoyer, Kay-Peter; Niendorf, Thomas; Grundmeier, Guido (Materials and Corrosion)

Cation-Induced Stabilization and Denaturation of DNA Origami Nanostructures in Urea and Guanidinium Chloride - Ramakrishnan, Saminathan; Krainer, Georg; Grundmeier, Guido; Schlierf, Michael; Keller, Adrian (Small)

Analysis of acid-base interactions at Al 2 O 3 (11-20) interfaces by means of single molecule force spectroscopy - Mosebach, Bastian; Ozkaya, Berkem; Giner, Ignacio; Keller, Adrian; Grundmeier, Guido (Applied Surface Science)

Scanning Kelvin probe blister studies of the delamination of epoxy films on organosilane modified ZnMgAl alloy coated steel - Grothe, R.; Wiesing, M.; Giner, I.; Meinderink, Dennis; Grundmeier, Guido (Materials and Corrosion)

Electropolymerization of acrylic acid on carbon fibers for improved epoxy/fiber adhesion - Bauer, Andreas; Meinderink, Dennis; Giner, Ignacio; Steger, Helmut; Weitl, Johann; Grundmeier, Guido (Surface and Coatings Technology)

A Contribution to explain the Mechanisms of Adhesive Wear in Plastics Processing by example of Polycarbonate - Bobzin, K.; Brögelmann, T.; Grundmeier, G.; de los Arcos de Pedro, Maria Teresa; Wiesing, M.; Kruppe, N.C. (Surface and Coatings Technology)

UHV AFM based colloidal probe studies of adhesive properties of VAlN hard coatings - Wiesing, M.; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido (Applied Surface Science)

Influence of PE-CVD and PE-ALD on defect formation in permeation barrier films on PET and correlation to atomic oxygen fluence - Mitschker, F; Steves, S; Gebhard, M; Rudolph, M; Schücke, L; Kirchheim, D; Jaritz, M; Brochhagen, M; Hoppe, Ch; Dahlmann, R; Böke, M; Benedikt, J; et al. (Journal of Physics D: Applied Physics)

Unearthing [3-(Dimethylamino)propyl]aluminium(III) Complexes as Novel Atomic Layer Deposition (ALD) Precursors for Al2O3: Synthesis, Characterization and ALD Process Development - Mai, Lukas; Gebhard, Maximilian; de los Arcos de Pedro, Maria Teresa; Giner, Ignacio; Mitschker, Felix; Winter, Manuela; Parala, Harish; Awakowicz, Peter; Grundmeier, Guido; Devi, Anjana (Chemistry - A European Journal)

Composite targets in HiPIMS plasmas: Correlation of in-vacuum XPS characterization and optical plasma diagnostics - Layes, Vincent; Monje, Sascha; Corbella, Carles; Schulz-von der Gathen, Volker; von Keudell, Achim; de los Arcos de Pedro, Maria Teresa (Journal of Applied Physics)

Nitridische und oxinitridische HPPMS-Beschichtungen für den Einsatz in der Kunststoffverarbeitung (Teil 2) - Bobzin, Kirsten; Grundmeier, Guido; Brögelmann, Tobias; de los Arcos de Pedro, Maria Teresa; Wiesing, Martin; Kruppe, Nathan C. (Vakuum in Forschung und Praxis)

Influence of organic surface chemistry on the nucleation of plasma deposited SiOxfilms - Hoppe, C; Mitschker, F; Giner, I; de los Arcos de Pedro, Maria Teresa; Awakowicz, P; Grundmeier, G (Journal of Physics D: Applied Physics)

Species transport on the target during high power impulse magnetron sputtering - Layes, V.; Monje, S.; Corbella, C.; Trieschmann, J.; de los Arcos de Pedro, Maria Teresa; von Keudell, A. (Applied Physics Letters)

Analysis of the inhibition of thermal degradation of molten polycarbonate at tool steel interfaces by thin TiAlN coatings - Wiesing, M.; de los Arcos de Pedro, Maria Teresa; to Baben, M.; Rueß, H.; Schneider, J.M.; Grundmeier, G. (Polymer Degradation and Stability)

Analysis of dispersive interactions at polymer/TiAlN interfaces by means of dynamic force spectroscopy - Wiesing, M.; de los Arcos de Pedro, Maria Teresa; Gebhard, M.; Devi, A.; Grundmeier, Guido (Physical Chemistry Chemical Physics)
Dispersion forces due to polarizable subsurface layers govern TiAlN/polymer interactions and decrease by 50% when oxidizing TiAlN to form TiAlO.

Adhesion of plasma-deposited silicon oxide barrier layers on PDMS containing polypropylene - Hoppe, C.; Mitschker, F.; Awakowicz, P.; Kirchheim, D.; Dahlmann, R.; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido (Surface and Coatings Technology)

Influence of the Surface and Heat Treatment on the Bond Strength of Galvanized Steel/Aluminum Composites Joined by Plastic Deformation - Hoppe, Christian; Ebbert, Christoph; Grothe, Richard; Schmidt, Hans Christian; Hordych, Illia; Homberg, Werner; Maier, Hans Juergen; Grundmeier, Guido (ADVANCED ENGINEERING MATERIALS)
The influence of a chemical or mechanical surface modification followed by different post-heat treatments on the bond strength of galvanized steel/ aluminum composites is studied. An incremental rolling process is used for joint formation based on plastic deformation. The morphology, the chemical state of the modified surfaces as well as the cross-section, and local potential distribution of the welded zone is characterized by different microscopic and spectroscopic methods. The stability of the joint is analyzed by a shear-force test in combination with microscopic failure analysis. A clear correlation between pre/post-treatment and the joint strength is observed.

Molecular Engineering of Aluminum-Copper Interfaces for Joining by Plastic Deformation - Hoppe, Christian; Ebbert, Christoph; Voigt, Markus; Schmidt, Hans Christian; Rodman, Dmytro; Homberg, Werner; Maier, Hans Juergen; Grundmeier, Guido (ADVANCED ENGINEERING MATERIALS)
Interface modification based on ultra-thin mercapto-propyl(trimethoxy) silane (MPTMS) films is shown to promote joining of copper and aluminum by plastic deformation followed by a heat treatment. The surface morphology and the surface chemistry of the metal substrates were analyzed by means of FE-SEM, XPS, and FT-IRRAS. The spectroscopic data show that the MPTMS film is crosslinked via Si-O-Si bonds and that stable Cu-S and Si-O-Al interfacial bonds are formed. The shear-force tests of the joints led to force displacement curves that are characteristic for a covalently bonded interface. Complementary cross sectional SEM and EDS analysis of the joint proved that a defect-free interface was formed without any measureable interdiffusion of metals across the interface or cracking of an oxide films.

Self-Assembly, Dynamics, and Polymorphism of hIAPP(20–29) Aggregates at Solid–Liquid Interfaces - Hajiraissi, Roozbeh; Giner, Ignacio; Grundmeier, Guido; Keller, Adrian (Langmuir)

Regular Nanoscale Protein Patterns via Directed Adsorption through Self-Assembled DNA Origami Masks - Ramakrishnan, Saminathan; Subramaniam, Sivaraman; Stewart, A. Francis; Grundmeier, Guido; Keller, Adrian (ACS Applied Materials & Interfaces)

Temperature-Dependent Charge Transport through Individually Contacted DNA Origami-Based Au Nanowires. - Teschome, B; Facsko, S; Schönherr, T; Kerbusch, J; Keller, Adrian; Erbe, A (Langmuir)

DNA annealing by Redβ is insufficient for homologous recombination and the additional requirements involve intra- and inter-molecular interactions. - Subramaniam, S; Erler, A; Fu, J; Kranz, A; Tang, J; Gopalswamy, M; Ramakrishnan, S; Keller, Adrian; Grundmeier, Guido; Müller, D; Sattler, M; Stewart, AF (Scientific Reports)